The H+-Translocating Inorganic Pyrophosphatase From Arabidopsis thaliana Is More Sensitive to Sodium Than Its Na+-Translocating Counterpart From Methanosarcina mazei - Pérez-Castiñeira, José R.; Serrano, Aurelio (Frontiers in Plant Science, 2020)
Overexpression of membrane-bound K+-dependent H+-translocating inorganic pyrophosphatases (H+-PPases) from higher plants has been widely used to alleviate the sensitivity toward NaCl in these organisms, a strategy that had been previously tested in Saccharomyces cerevisiae. On the other hand, H+-PPases have been reported to functionally complement the yeast cytosolic soluble pyrophosphatase (IPP1). Here, the efficiency of the K+-dependent Na+-PPase from the archaeon Methanosarcina mazei (MVP) to functionally complement IPP1 has been compared to that of its H+-pumping counterpart from Arabidopsis thaliana (AVP1). Both membrane-bound integral PPases (mPPases) supported yeast growth equally well under normal conditions, however, cells expressing MVP grew significantly better than those expressing AVP1 under salt stress. The subcellular distribution of the heterologously-expressed mPPases was crucial in order to observe the phenotypes associated with the complementation. In vitro studies showed that the PPase activity of MVP was less sensitive to Na+ than that of AVP1. Consistently, when yeast cells expressing MVP were grown in the presence of NaCl only a marginal increase in their internal PPi levels was observed with respect to control cells. By contrast, yeast cells that expressed AVP1 had significantly higher levels of this metabolite under the same conditions. The H+-pumping activity of AVP1 was also markedly inhibited by Na+. Our results suggest that mPPases primarily act by hydrolysing the PPi generated in the cytosol when expressed in yeast, and that AVP1 is more susceptible to Na+ inhibition than MVP both in vivo and in vitro. Based on this experimental evidence, we propose Na+-PPases as biotechnological tools to generate salt-tolerant plants.